Moral Responsibility and Ontology
VI, 277 p.
Keywords: Ton van den Beld This book is one of the results of the international conference on Moral Responsibility and Ontology, which was held at Utrecht University in 1 June 1998. It contains a selection of the revised versions of the papers discussed at the conference. The theme is in need of some clarification. In the first place, 'responsi bility' is an ambiguous term. Although addition of the adjective 'moral' reduces the variety of its meanings (for example, moral responsibility cannot be confused with causal responsibility), different interpretations are still possible. Thus, the care of dependent children is a parental moral responsibility. That is, parents have the moral obligation to care for their children. It is their moral task, or role, to do so. If they fail to fulfil this obligation, they might be morally responsible for the result of this failure. Here, another meaning of 'moral responsibility' is involved: the children's misery might be imputed to their parents. They may be liable to blame. Moral responsibility in this sense is what the conference was and this book is about. It is about the conditions which must be met for a person to be justly held responsible for his or her moral faults and failures.